Governance Disclosure, Policy Coherence, and Organizational Performance in Private Universities in Somalia - Hassan, Hassan Sheikh; Messah, Omboi Bernard (Veredas do Direito, 2026)
This study examines how governance disclosure and policy coherence relate to organizational performance in private universities in Somalia. In fragile higher education systems, institutional effectiveness depends not only on formal governance structures but also on the transparency of governance information and the internal alignment of institutional policies. Using a qualitative design based on secondary document analysis, the study examines publicly available governance and policy materials from four private universities in Somalia. Guided by agency theory, stewardship theory, and resource dependence theory, the analysis finds that universities with clearer governance disclosure and more coherent policy frameworks tend to demonstrate stronger documentary indicators of organizational performance, particularly in strategic alignment, administrative structure, and institutional visibility. While the findings do not establish causality, they suggest that transparency and policy alignment are important indicators of governance quality in fragile higher education contexts. The study contributes to the literature by showing that governance disclosure and policy coherence are practical dimensions of institutional capacity and credibility in private universities in Somalia.